Exile of the Beat King: Eden, Moloch, and the Mythic American Journeys of Jack Kerouac (AmeriQuests, 2004)
Maynard argues that Kerouac’s relationship with exile extends beyond On The Road, a novel that has been read in many ways, ranging from an American travelogue to a psychological portrait of postwar U.S. In his essay, Maynard tracks the cultural influence of On The Road. He addresses the uncomfortable mythologization of Kerouac’s novel as a fiction of psychological exile and examines the implications of a narrative in which the author himself becomes a fictional character.Maynard argumenta que la relación de Kerouac con el exilio se extiende más que en On The Road, una novela que ha sido leída desde muchos puntos de vista, en los límites de una película de viaje americana a un retrato psicológico de los EEUU posguerra. En su ensayo, Maynard considera la influencia cultural de On The Road. Se dirige a la mitologicación incómoda de la novela de Kerouac como ficción del exilio psicológico y examina las implicaciones de una narrativa en la cual el autor mismo se convierte en un personaje ficticio.Maynard argumenta que a relação de Kerouac com exílio estende-se acima de On The Road, uma novela que tem sido interpretado de muitas maneiras distintas, entre elas como uma crónica de viagem americana a um retrato psicológico dos E.U. na pós-guerra. Em seu trabalho, Maynard considera a influência cultural de On The Road. Ele considera a mitologização incómoda da novela de Kerouac como uma ficção de exilo psicológico e examina as implicações duma narrativa em que o autor mesmo chega a ser pessoa fictícia.Maynard affirme que la relation de Kerouac avec l’exil va au-delà de son roman On The Road, qui a été interprété de plusieurs manières, allant du récit de voyage américain au portrait psychologique des Etats-Unis d’après-guerre. Dans son essai, Maynard part à la recherche de l’influence culturelle de On The Road. Il pose le problème de la mythification gênante du roman de Kerouac comme la fiction d’un exil psychologique, et il examine les implications d’un récit dans lequel l’auteur lui-même devient un caractère fictif.